Designing Self-Inhibitory fusion peptide analogous to viral spike protein against novel severe acute respiratory syndrome (SARS-CoV-2) - Singh I.; Singh S.; Ojha K.K.; Yadav N.S. (My University, 2025)
COVID-19 is a highly contagious viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is declared pandemic by the World Health Organization (WHO). The spike protein of SARS-CoV-2 is a key component playing a pivotal role in facilitating viral fusion as well as release of genome into the host cell. Till date there is no clinically approved vaccine or drug available against Covid-19. We designed four hydrophobic inhibitory peptides (ITPs) based on WWIHS (Wimley and White interfacial hydrophobicity scale) score, targeting the HR1 domain of spike protein. Two inhibitory peptides out of four have a strong affinity to the hydrophobic surface of HR1 domain in pre-fusion spike protein. The MD simulation result showed the strong accommodation of ITPs with HR1 domain surface. These self-inhibitory peptides mimic the function of HR2 by binding to HR1 domain, thus inhibiting the formation of HR1-HR2 post-fusion complex, which is a key structure for virus-host tropism. Communicated by Ramaswamy H. Sarma. © 2021 Informa UK Limited, trading as Taylor & Francis Group.